Ilmu Komunikasi Dalam Desain Penelitian Kualitatif - Neka Fitriyah (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2026)
Communication is a scientific discipline that can be studied in a variety of methods, various approaches, and various theories. However, communication science as a science refers to proven scientific methods to gain a deep understanding of an eventTherefore, this study aims to describe qualitative research design in diverse perspectives that can be applied to communication science. The results of this study illustrate that qualitative research is a series of interpretive practices that use many methods in examining research problems. Qualitative research is intended as an effort to explain a phenomenon related to what individuals experience holistically through the description of words, language that takes place in a natural context with a variety of methods. The emphasis of qualitative research lies in processes and interactions, the instruments are self-research, logic that is built deductively, data in the form of narrative and descriptive, data collection through observation, interviews, FGDs, documentation. Theory in qualitative research is temporary and dynamic. Qualitative research has five approaches, namely, narrative, phenomenology, ethnography, grounded theori and case studies. The strategy of data analysis is carried out by making contradictions and comparisons between variables, displaying research findings in tables, figures, diagrams and comparing with standard cases. This research contributes to the development and strengthening of understanding in designing qualitative communication research. Qualitative research has five approaches, namely, narrative, phenomenology, ethnography, grounded theori and case studies. The strategy of data analysis is carried out by making contradictions and comparisons between variables, displaying research findings in tables, figures, diagrams and comparing with standard cases. This research contributes to the development and strengthening of understanding in designing qualitative communication research.